Property of a noblewoman : a novel - Steel, Danielle (London Bantam, 2016)
"Property of a Noblewoman is the fascinating, moving new novel from Danielle Steel, whose many #1 New York Times bestselling tales have made her one of America's most beloved writers"--
Keywords: Young women -- Fiction; Heirlooms -- Fiction; FICTION / Contemporary Women; FICTION / Sagas; FICTION / Romance / Contemporary; Mystery fiction; Love stories